Implementasi AES ECB dan Hashing MD5/SHA-256 Pada Aplikasi Penyuratan Android - Fajar Febriyadi; Fitra Kurnia; Nazruddin Safaat Harahap; Febi Yanto; Pizaini Pizaini (Journal of Computer System and Informatics (JoSYC), 2023)
The Riau Ministry of Religion Regional Office is still archiving assignment letters and official travel letters manually. The staff who take care of the correspondence section, namely personnel and legal unit staff, do not have an application that facilitates the activities of assignment letters and official travel letters to simplify filing and data containing certain information contained in letters which include assignment letters and official travel letters. Security is important because it relates to data. Therefore, a correspondence application was created to support the correspondence activities of the Riau Ministry of Religion Regional Office and make it easier for staff in the Civil Service and Legal unit to properly manage assignment letters and official travel letters as well as control books. Android application development uses the waterfall method and the ECB (Electronic Code Book) mode AES algorithm and MD5/SHA-256 hashing for security. By building this application, it will be easier for leaders and employees to exchange letters and confidential information, guaranteed security and the application built can be used by users easily. The results of the Black Box testing carried out on the application produced the expected output and the UAT test obtained a score of 89%. Application testing on sentences, Jpg, Png and PDF files has a fairly high level of security using statistical analysis methods, namely bit frequency testing, autocorrelation, 0/1 bit distribution, entropy.